AB0636 INFLUENCE OF CARDIOVASCULAR RISK FACTORS ON NAILFOLD VIDEOCAPILLAROSCOPY IN THE STUDY OF CONNECTIVE TISSUE DISEASES. (June 2019) - Benavent, Diego; Nuño, Laura; Bonilla, Gemma; Peiteado, Diana; Plasencia, Chamaida; Navarro-Compán, Victoria; Monjo, Irene; Villalva, Alejandro; García-Carazo, Sara; Tornero, Carolina; Bogas, Patricia; Fernández, Elisa; et al.
Abstract : Background: Nailfold videocapillaroscopy is a non-invasive technique used to assess Raynaud syndrome. It is mainly used for the early diagnosis of connective tissue disorders (CTD) such as systemic sclerosis. There is some evidence that capillaroscopy findings may be altered by microcirculation abnormalities in patients with cardiovascular risk factors (CVRF). Objectives: to analyze the influence of cardiovascular risk factors on naildfold capillaroscopy in patients with Raynaud or suspect of CTD. Methods: An observational and descriptive study of consecutive patients that underwent a videocapillaroscopy examination for the study of Raynaud syndrome was conducted. A "Capiscope" model videocapilaroscope from Optilia was used, with a fixed magnification of 200x. Examination was made on 8 hand fingers, with 2 images per finger. The patients had to be at least 30 minutes in a fixed warm temperature room and without smoking 1 hour before the performance of the test. The following capillaroscopic parameters were considered: nailfold morphology, capillary loop enlargements, megacapillaries, microhaemorrhages, avascular areas and signs of neoangiogenesis. Demographic information (including age, gender and previous diagnosis) and cardiovascular risk factors (including arterial hypertension (HT), diabetes mellitus (DM), dyslipidemia (DL) and smoking habit), were collected. The influence of cardiovascular risk factors on naildfold capillaroscopy was analyzed, using univariate and multivariate logistic regression models, adjusted for possible confounders. Results: Out of the 136 included patients, 91% were women. Mean age was 54, 6 ± 18, 7 years. Raynaud syndrome was reported in 83% patients, with a mean duration of 6, 1 ± 5, 7 years and 12% of the patients had a previous diagnosis of CTD, including systemic lupus erythematosus (5%), systemic sclerosis (4%), undifferentiated connective tissue disorder (2%) and mixed connective tissue disease (1%). Regarding CVRF, HT was observed in 25%, DM in 7%, DL in 23% and past or current smoking habit in 32%. Capillaroscopic findings were: loop enlargements (81%), megacapillaries (30%), microhaemorrhages (46%), signs of neoangiogenesis (71%) and avascular areas (20%). Regarding the capillaroscopic pattern, 46% presented a normal or nonspecific pattern; 31% a microangiopathy pattern and 23% a scleroderma pattern (of which 58% had an early or active scleroderma pattern and 42% a late scleroderma pattern). A new diagnosis of CTD was made in 24 patients (18% of the cohort). In the group of patients without CTD, HT was associated with microhaemorrhages (p = 0.02) and avascular areas (p = 0.007), and there was a tendency to association between smoking habit and megacapillaries (p = 0.08). After adjusting for confounding factors for this group, an association between CTD and microhaemorrhages (OR = 1.9; p = 0.01) and avascular areas (OR = 2.12; p = 0.007) was found. The multivariate study showed no relationship between CVRF and capillaroscopy patterns. Conclusion: In our cohort we found an increased frequency of microhaemorrhages and avascular areas in the naildfold capillaroscopy in patients with arterial hypertension. The presence of cardiovascular risk factors could have an influence on the microvasculature and therefore on the findings of the capillaroscopy. More studies are required to better assess these findings. References: [1] Cutolo, et al., Best Pract Res Clin Rheumatol.2013;27:237-248. Disclosure of interests: Diego Benavent: None declared, Laura Nuño: None declared, Gemma Bonilla: None declared, Diana Peiteado: None declared, Chamaida Plasencia Speakers bureau: Pfizer, MSD, Victoria Navarro-Compán: None declared, Irene Monjo: None declared, alejandro Villalva: None declared, Sara García-Carazo: None declared, Carolina Tornero: None declared, Patricia Bogas Grant/research support from: non restricted grant from Sanofi, Elisa Fernández: None declared, Miguel Bernad: None declared, ana Castilla: None declared, Pilar aguado: None declared, Maria-Eugenia Miranda-Carus Grant/research support from: Roche Pharma, BMS, Eugenio de Miguel: None declared, alejandro Balsa Grant/research support from: abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly